Factors associated with vitamin D deficiency in health care workers exposed to SARS-CoV-2: a cross-sectional study - Villasis-Keever, Miguel Angel; Zurita-Cruz, Jessie Nallely; Garduño-Espinosa, Juan; López-Alarcón, Mardya; Barradas Vázquez, Aly Sugey; Miranda-Novales, María Guadalupe; Parra-Ortega, Israel; López-Martinez, Briseida; García, Heladia; Klünder-Klünder, Miguel (Frontiers in Nutrition, 2024)
Introduction Globally, up to 76.6% of the population may be affected by vitamin D (VD) deficiency, which has been linked to increased morbidity and mortality from COVID-19. This underscores the importance of further research into VD supplementation, particularly for health care workers, who are at higher risk due to indoor work environments and dietary challenges associated with shift schedules. Objective This study aimed to identify factors associated with VD deficiency in Mexican health care workers exposed to SARS-CoV-2. Materials and methods We conducted a cross-sectional study from June 2020 to January 2021 among frontline health care workers treating hospitalized COVID-19 patients. Blood samples were collected to measure 25-hydroxy VD levels via radioimmunoassay. We also assessed previous COVID-19 infection and comorbidities that could influence VD levels. Results The study included 468 health care workers. The median serum VD concentration was 16.6 ng/mL. VD deficiency was found in 69.4% (n = 325) of participants, while only 5.1% (n = 24) had normal levels. Those with type 2 diabetes (13.3 ng/mL vs. 17.1 ng/mL) or obesity (15.7 ng/mL vs. 17.1 ng/mL) had significantly lower VD levels than their counterparts (p < 0.001 and p = 0.049, respectively). No significant differences were found among participants with high blood pressure. Multivariate analysis revealed that type 2 diabetes was independently associated with VD deficiency. Conclusion There is a high prevalence of VD deficiency among health care workers, which is potentially linked to both personal health factors and occupational conditions.